Large Anterior Mediastinal Mass and Cardiac Infiltration at Diagnosis in a Child With T-cell Acute Lymphoblastic Leukemia. Issue 2 (1st March 2022) - Meyer, Erin J.; Umaretiya, Puja; Vrooman, Lynda M.
Abstract : While anterior mediastinal masses are a common presenting feature of T-cell acute lymphoblastic leukemia, cardiac leukemic infiltration is an exceedingly rare extramedullary manifestation. We report a 4-year-old female with new-onset T-cell acute lymphoblastic leukemia who was found to have a large interventricular septal mass upon initial presentation. This patient required a unique management approach with serial echocardiograms, continuous telemetry, and hemodynamic monitoring with close surveillance for ventricular ectopy. Given a good response to traditional leukemia therapy, the cardiac mass was presumed to have been a focal infiltrate of leukemic cells.